The last of the Mohicans - Martin, Les; Stirnweis, Shannon; Cooper, James Fenimore (New York : Random House, 1993)
A simplified retelling of the story about the exploits of a young white man and his Mohican Indian friends during the French and Indian War.
Keywords: Bumppo, Natty (Fictitious character); Mohegan Indians; Frontier and pioneer life; Mohegan Indians; Indians of North America